The Strategic Role of Social Networks in Academic Leadership Development - Stawnychko, Leda (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2024)
University leaders navigate a complex and dynamic environment, balancing the diverse expectations of students, faculty, policy makers, and governmental bodies. Proficiency in these roles requires deep academic understanding, contextual knowledge, and effective management and leadership skills. This study explored how faculty members serving as department chairs developed their leadership capacity when entering the role. The investigation utilized social network theory and a leadership development model to examine department chairs’ experiences at a Canadian research-intensive university. It employed a qualitative research approach combining constructivist philosophy, case study design, and inductive research techniques. Drawing on the key themes of role entry, role understanding, and skill development, the study found that social networks played a central role in the participants’ leadership development. Post-secondary institutions may consider supporting leadership networks and providing equitable access to learning opportunities to increase academic leadership capacity.